Ontogeny of Innate T Lymphocytes – Some Innate Lymphocytes are More Innate than Others - Vermijlen, David; Prinz, Immo (Frontiers in Immunology, 2014)
Innate lymphocytes have recently received a lot of attention. However, there are different ideas about the definition of what is “innate” in lymphocytes. Lymphocytes without V(D)J-rearranged antigen receptors are now termed innate lymphoid cells (ILCs) and include cells formerly known as NK cells. Also, lymphocytes that are innate should be able to recognize microbial or stress-induced patterns and react rapidly without prior sensitization, as opposed to adaptive immune responses. Formally, genuine innate lymphocytes would be present before or at birth. Here we review the ontogeny of human and mouse innate T lymphocyte populations. We focus on γδ T cells, which are prototype lymphocytes that often use their V(D)J rearrangement machinery to generate genetically encoded predetermined recombinations of antigen receptors. We make parallels between the development of γδ T cells with that of innate aβ T cells (invariant (i)NKT and mucosa-associated invariant T (MAIT) cells) and compare this with the ontogeny of innate B cells and innate lymphoid cells (ILCs, including NK cells). We conclude that some subsets are more innate than others, i.e. innate lymphocytes that are made primarily early in utero during gestation while others are made after birth. In practice, a ranking of innateness by ontogeny has implications for the reconstitution of innate lymphocyte subsets after hematopoietic stem cell transplantation (HSCT).